Solubility enhancement of crystalline nanocellulose (cnc) via dissolution of oil palm empty fruit bunches (opefb) - Koo, You Ying (School of Bioprocess Engineering, University Malaysia Perlis, 2017)
Oil palm empty fruit bunch (OPEFB) is one of the lignocellulosic waste materials that found abundantly in nature. Substantial amount of these residues create environmental problem if not dispose properly. However, by producing valuable product which is crystalline nanocellulose (CNC) from OPEFB able to simplify the disposal process. Since there is limited study on solubility enhancement of CNC from OPEFB by using hydrochloric acid, the aim of this project was to optimize the operating conditions of production of crystalline nanocellulose (CNC). Three operating parameters of solid to liquid ratio, reaction time and solvent concentration were studied. All three parameters were optimized for maximum yield of CNC by using Design of Experiment (DOE) software. From this project, the optimum condition to obtain the highest solubility of CNC from the dissolution of OPEFB of 32.13% has been found to be at solid to liquid ratio of 0.05, reaction time of 136.81 minutes and solvent concentration of 57.81 wt%. The solubility of CNC achieved after optimization process shows an increment of 16 % by comparing with others researchers. The CNC produced was also studied for its characterization using Fourier Transform Infrared Spectorcopy (FTIR) and Scanning Electron Microscopy (SEM) analysis. The novelty of this project is that CNC was able to be produced from a variety of lignocellulosic material which is sustainable and renewable natural resource.